River community agency in mitigating disaster risk - Ramdhon Akhmad; Zunariyah Siti; Demartoto Argyo (E3S Web of Conferences)
Community plays a central role in disaster risk mitigation discourse and practice. This article explains important factor affecting the emergence of river community agency in disaster risk mitigation and agency form and pattern performed by river community. River Community in Yogyakarta city is selected to be the research location using multiple case study. The result of research shows that river community agency is affected ecological complaint and disaster experience harmful materially and non-materially. The agency pattern performed consists of structural and cultural agencies. Structural pattern gives emphasis on actions related to the attempt of restoring one of river’s functions as disaster organizer. The form of structural agency is manifested into some actions: cleaning river, saving river border, and organizing slums. Cultural agency gives emphasis on the attempt of improving environmental consciousness and interest in increasing the capacity of suppressing vulnerability. The form of cultural agency is facilitated through river school playing an important role in improving knowledge and capacity concerning environment and disaster. The two agency patterns become an integrated strategy to create a disaster-resilient community.